2017
DOI: 10.1038/s41598-017-09321-y
|View full text |Cite
|
Sign up to set email alerts
|

Nevirapine induced mitochondrial dysfunction in HepG2 cells

Abstract: Nevirapine (NVP) is a non-nucleoside reverse transcriptase inhibitor frequently used in combination with other antiretroviral agents for highly active antiretroviral therapy (HAART) of patients infected with the human immunodeficiency virus type 1 (HIV-1). However NVP can cause serious, life-threatening complications. Hepatotoxicity is one of the most severe adverse effects, particularly in HIV patients with chronic hepatitis C virus co-infection as these patients can develop liver toxicity after a relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…However, the several side effects, such as rash, nausea, fatigue, headache, vomiting, diarrhoea, and pain, have been reported after oral intake of NVP (Chowta et al 2018). It has been further reported that in vitro direct treatment of NVP is induced to the induction of hepatotoxicity by mitochondrial dysfunction and apoptosis in HepG2 cells (Wongtrakul J, et al 2016; Paemanee et al 2017). The treatment of NVP has also been demonstrated to delay cell growth in the various types of cells, especially cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the several side effects, such as rash, nausea, fatigue, headache, vomiting, diarrhoea, and pain, have been reported after oral intake of NVP (Chowta et al 2018). It has been further reported that in vitro direct treatment of NVP is induced to the induction of hepatotoxicity by mitochondrial dysfunction and apoptosis in HepG2 cells (Wongtrakul J, et al 2016; Paemanee et al 2017). The treatment of NVP has also been demonstrated to delay cell growth in the various types of cells, especially cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two-dimensional gel electrophoresis separation of 300 μg of enriched phosphoproteins was performed independently in triplicate as described previously 54 .…”
Section: Methodsmentioning
confidence: 99%
“…Protein spots showing differential phosphorylation were removed and subjected to in-gel tryptic digestion and mass spectroscopic analysis essentially as described previously 54 . The MS/MS spectrometry data were searched against the NCBI database using the MASCOT search engine, as described elsewhere 54 . Functional analysis of identified phosphoproteins was performed using STRING (Search Tool for the Retrieval of Interacting Genes/Proteins) version 11.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HepG2 cells, due to their high mitochondrial DNA and organelles contents, remain a model of choice for the study of compound-induced mitochondrial dysfunction (Poloznikov et al 2018). Applied transcriptomic and proteomic analyses to this cell model, Jiang et al (2015a) and Paemanee et al (2017) explained the mechanisms of mitochondrial dysfunction associated with APAP and nevirapine (NVP) administrations. Using a HepG2-based in vitro cytokine synergy model, an attempt has been made to investigate the relationship between inflammation and drug idiosyncrasy (Jiang et al 2017).…”
Section: Hepatocellular Carcinoma Cell Linesmentioning
confidence: 99%